Pengaruh Proses Solution Treatment dan Shot Peening Terhadap Kekuatan Mekanik dan Struktur Mikro Baja Mangan Austenitik Untuk Komponen Frognose Rel - Wahyu, Wahyu Tian; Ramdan, Raden Dadan (SPECTA Journal of Technology, 2025)
Wessel is a part of the railway track which functions as track switching. One of the components of Wessel, which is made through the casting process is called frognose. Frognose is the most critical component in the Wessel crossing, as it must withstand the impact load caused by the movement of train wheels. The production of frognose follows the EN 15689 standard and the Minister of Transportation Regulation of the Republic of Indonesia No. 60 of 2012. Austenitic manganese steel ASTM A 128 Grade C is chosen as the main material. This austenitic manganese steel has high-strain hardening properties when subjected to static, dynamic, and impact loads on its surface. In this study, a heat treatment process is used to improve the mechanical properties and carbide solubility of the casting results. Cooling the object from the casting process causes carbide growth which is caused by the cooling rate. Therefore, solution treatment is necessary to dissolve the carbides. The solution treatment process is carried out at various temperatures 1075ºC, 1150ºC, and 1225ºC. Subsequently, the optimized material from the solution treatment is subjected to shot peening deformation. Based on the research results, the solution treatment process at 1150ºC temperature shows the best toughness, thus it will be continued with the shot peening deformation process. The deformation caused by the shot peening process is able to change the crystal orientation by forming twinning, thereby increasing the material hardness value. The best mechanical properties are obtained in sample ST2 followed by the SP12 process with a combination of hardness value of 35 HRC at a depth of 0.05mm; impact energy of 82,92 joule/cm2 and mostly carbide-free microstructure.